RELEVANSI MASLAHAH DALAM FATWA MUI TENTANG JUAL BELI EMAS DIGITAL TERHADAP PERLINDUNGAN KONSUMEN - Syah, Irwan; Hanani, Silfia (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
The rise of digital transactions has led to the practice of digital gold trading, which was later endorsed by the Indonesian Ulema Council (MUI). This fatwa reflects an effort to align sharia principles with the digital economy, particularly in protecting Muslim consumers. This study analyzes the relevance of the maslahah (public interest) concept in the MUI fatwa on digital gold trading and examines its role in consumer protection. Using a normative library research method, data were collected from MUI fatwas, fiqh literature, and Islamic consumer protection regulations. The findings indicate that the fatwa incorporates maslahah by promoting easier and more inclusive sharia-compliant transactions. However, challenges remain, including ambiguous contracts, price volatility, and inadequate legal safeguards. While the fatwa reflects a positive step toward harmonizing Islamic principles with modern finance, further regulatory enhancement and public education are essential to ensure stronger consumer protection in sharia-based digital gold transactions.